Problems of Nonlinear Mechanics and Physics of Materials - Andrianov, Igor V.; Manevich, Arkadiy I.; Mikhlin, Yuri V.; Gendelman, Oleg V. (Advanced Structured Materials,, 2019)
This book presents contributions on the current problems in a number of topical areas of nonlinear dynamics and physics, written by experts from Russia, Ukraine, Israel, Germany, Poland, Italy, the Netherlands, the USA, and France. The book is dedicated to Professor Leonid I. Manevitch, an outstanding scholar in the fields of Mechanics of Solids, Nonlinear Dynamics, and Polymer Physics, on the occasion of his 80th birthday.